The Process of Globalization from the Point of View of Synergetic Patterns - V. V. Tuzov (Дискурс, 2022)
Introduction. The article examines the process of globalization through the prism of synergetics. The urgency of the problem of globalization is beyond doubt, it is enough just to turn to the news channels. The purpose of the work is to show the inconsistency of globalization promoted by Western countries, because it contradicts the laws that determine the process of self-organization of open nonequilibrium systems.Methodology and sources. The article applies the laws of dialectics and the theory of selforganization. The research sources used works on the problems of globalism (I. Wallerstein, S.P. Lapaev, I.F. Kefeli, etc.), the laws of the development of the historical process  (S.D. Bodrunov, V.V. Tuzov), the laws of the processes of self-organization of open nonequilibrium systems (I. Prigozhin, G. Haken, E.N. Knyazeva and S.P. Kurdyumov and etc.).Results and discussion. The author comes to the conclusion that it is impossible to realize the process of globalization in the form that the United States and its allies are trying to implement, because this contradicts both the laws of the historical process and the laws of self-organization that the modern stage of development of society obeys. It is impossible to unite countries with different cultures, religions, different economic levels of development, etc. on equal terms, because from the point of view of synergetics it is impossible for systems that exist in a different “tempworld”. There may be possible subordination and exploitation, but not partnership. The unification of all countries around one center also contradicts economic laws, because competition and the development of a market economy will disappear. Moreover, it contradicts the laws of self-organization. A system striving for expansion contains within itself its opposite, which is the desire for dissipation (dispersion).Conclusion. The author of the article concludes that globalization in the form in which it is carried out by Western countries, since it contradicts the laws of the market economy and the laws of self-organization, is possible only under pressure. The end of forceful coercion triggers the dissipation mechanism, which leads to the degradation of the system and its simplification.